Outcome of patients of acute kidney injury in chronic liver disease - Varsha Tiwari; Ashish Purohit; Sanjay Parashar (International Journal of Medical Research and Review, 2019)
Introduction: Chronic liver disease (CLD) is also a common clinical problem afflicting mankind. Occurrence of Acute kidney injury in patients with chronic liver disease is frequent finding which makes prognosis of CLD even poorer.Material and methods: A prospective cohort observational study on 100 adult patients of chronic liver disease with AKI conducted over a period of 24 months from August 2016 to August 2018 at Sri Aurobindo medical college and postgraduate institute. Detailed clinical examination and biochemical tests were done. Univariate and multivariate logistic regression (odds ratio) analyses were used.Results: 87% were males and 13% were females. Maximum no. of patients found in AKI stage III 40% followed by stage I 36% then stage II 24%. Among these 31% patient recover after treatment, 26% partially recovered and 43% patient didn’t response to treatment. Overall 75% survived while 25% died in this study.Conclusion: Majority of Patients with Prerenal AKI had full recovery, as compared to HRS-AKI and intrinsic AKI where full recovery was less common. Patients in stage 1 AKI had more proportion of patients with full recovery than stages 2 and 3. Regarding outcome, Patients in stage 1 and stage 2 has higher survival rates as compared to stage 3, which is statistically significant.